Educational Landscape in Indonesia in 2023: Challenges and Opportunities - Usman Jayadi; Arman Harahap; Aslan Aslan (Lafadz Jaya Publisher, 2023)
This article examines the state of education in Indonesia in 2023, focusing on both the challenges and opportunities facing the system. Education in Indonesia has undergone significant transformation over the past decade, but several barriers remain, such as disparities in access, quality, and infrastructure between urban and rural areas. Despite these challenges, recent reforms and the increased use of technology have provided promising avenues for improvement. The study analyzes the national education policies, including the impact of the Merdeka Curriculum, and evaluates the role of digital learning platforms in addressing the educational needs of Indonesia’s vast population. Additionally, the article highlights key issues such as teacher training, student engagement, and education for sustainable development. By examining both the progress made and areas requiring further attention, this paper offers a comprehensive view of the Indonesian educational system in 2023. The findings suggest that while substantial improvements have been made, systemic inequities and the rapid pace of technological integration pose both challenges and opportunities for educators, policymakers, and students alike.